The Challenge of Lithium Metal Anodes for Practical Applications. Issue 7 (16th April 2019) - Chen, Yuqing; Luo, Yang; Zhang, Hongzhang; Qu, Chao; Zhang, Huamin; Li, Xianfeng
Abstract: Lithium metal anodes are considered as the "Holy Grail" to achieve high energy density of rechargeable batteries. In the past 50 years, enormous progress has been made to solve the long‐term disturbing issues of poor safety and cyclic stability for lithium metal batteries (LMBs). However, there is still a long distance to realize the application of LMBs. In this review, the mechanisms of dendrite growth and solid electrolyte interphase (SEI) properties are first summarized to figure out the impact factors of the two issues. Advanced strategies are subsequently discussed by regulating different impact factors like current density, overpotential, and interfacial properties. To promote the practical application of LMBs, it is concluded that future research should focus on constructing robust SEI layers, either in liquid electrolytes or solid‐state electrolytes. Moreover, promising research directions and development suggestions are also provided in this review. Abstract : The application of lithium metal batteries (LMBs) is discussed with the fundamental issues of lithium metal anode, the impact factors of the issues, and the current advanced strategies by regulating different impact factors. Constructing robust solid electrolyte interphase layer is a promising solution to realize the practical application of LMBs.